Dinamika Kepribadian Tokoh Utama Dalam Novel Jisatsu Yotei Bi Karya Akiyoshi Rikako - Teting Lairabu (Program Studi Sastra Jepang, Universitas Komputer Indonesia Bandung, 2018)
Abstract This study aims to explain death wish in the characterization of the main character. This research uses a descriptive analysis method with the psychology literature approach. The sources of data used were the novel Jisatsu Yotei Bi by Akiyoshi Rikako (2016) and the Indonesian translation of the novel, Scheduled Suicide Day (2017). The object of this research is a quotation in the form of narrative. The results of this study are the main character has a desire to die and it is shown by her always thinking about death and finding out in one website about ways to die that she thinks are comfortable and appropriate. Keywords: Personality Dynamics, Death Wish, Characterization, Psychology Literature.